2013
DOI: 10.1007/s10653-013-9539-6
|View full text |Cite
|
Sign up to set email alerts
|

The importance of solid-phase distribution on the oral bioaccessibility of Ni and Cr in soils overlying Palaeogene basalt lavas, Northern Ireland

Abstract: Potentially toxic elements (PTEs) including nickel and chromium are often present in soils overlying basalt at concentrations above regulatory guidance values due to the presence of these elements in underlying geology. Oral bioaccessibility testing allows the risk posed by PTEs to human health to be assessed, however bioaccessibility is controlled by factors including mineralogy, particle size, solid phase speciation and encapsulation. X-ray diffraction (XRD) was used to characterise the mineralogy of 12 soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
5
36
0
Order By: Relevance
“…As a result, the chemistry of these soils, groundwater and vegetation will differ from site to site and might represent, in varying degree, a geogenic source of elements with possible health implications for humans (Cox et al, 2013;Kabata-Pendias and Mukherjee, 2007;Kelepertzis and Stathopoulou, 2013;Selinus et al, 2005). Ranges in natural geochemical variability combined with bioaccessibility and ecotoxicological studies may then provide an objective basis for setting appropriate risk-related regulatory levels in such areas.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the chemistry of these soils, groundwater and vegetation will differ from site to site and might represent, in varying degree, a geogenic source of elements with possible health implications for humans (Cox et al, 2013;Kabata-Pendias and Mukherjee, 2007;Kelepertzis and Stathopoulou, 2013;Selinus et al, 2005). Ranges in natural geochemical variability combined with bioaccessibility and ecotoxicological studies may then provide an objective basis for setting appropriate risk-related regulatory levels in such areas.…”
Section: Introductionmentioning
confidence: 99%
“…Cd (Denys et al, 2012). However , as oral bioaccessibility can be affected by a number of factors 98 including mineralogy, particle size, solid-phase speciation and encapsulation (Cave et Cox et al (2013) found that bioaccessible Cr in the 111 basaltic soils of Northern Ireland is strongly correlated with total Cr and Fe2O3, indicating that Cr is 112 predominantly present in phases associated with Fe2O3 that have relatively low bioaccessibility. 113…”
mentioning
confidence: 99%
“…Non-specific sequential extractions (CISED), showed that the majority of Cr was present in oxides, with 114 a only a very small component present in clays (Cox et al, 2013). In contrast Cox et al (2013) found 115 that bioaccessible Ni (both G and GI) was not strongly correlated with total Ni, most of the major oxides 116 or Soil Organic Carbon (SOC).…”
mentioning
confidence: 99%
“…Over the years the emphasis has been on leaded fuel (Oudijk, 2010;Nriagu et al, 1996;Romieu et al, 1992), but there are many other activities that release Pb into the environment particularly in the urban/industrial setting: activities such as metal mining, smelting and processing, the use of Pb in lead-acid batteries, pigments, alloys, lead wool, chemical manufacturing, cables, solders, plumbing components, food cans, coal combustion, lead based paint (including that in road markings), and industrial waste (Ajmore-Marsan and Biasioli, 2010;Brown and Longoria, 2010;De Silva et al, 2016;Laidlaw and Taylor, 2011;Mielke et al, 2010;Shen et al, 2002). Studies have shown that the Pb retained in soil/dust because of anthropogenic activity typically occurs in highly bioavailable, exchangeable and carbonate forms, whereas, Pb retained because of natural occurrence is often found in residual or lessbioavailable forms (Chlopecka et al, 1997;Cox et al, 2013;Palumbo-Roe et al, 2013;Pelfrêne et al, 2012;Laidlaw and Filippelli, 2008;Reis et al, 2014;Ruby et al, 1994). Direct exposure to urban dust through inhalation is expected thus the respiratory tract is a potentially significant pathway through which urban dusts can enter the human body.…”
Section: Introductionmentioning
confidence: 99%